The financial literacy of students and investment decisions in the Indonesia stock exchange - Murviana Koto; Delyana Rahmawany Pulungan (Proceedings of AICS - Social Sciences, 2017)
This study aims to analyze how the role of student financial literacy is in influencing the investment decision in the Indonesia Stock Exchange. The populations are the students of Economic and Business Faculty in University of Muhammadiyah Sumatera Utara. This is an explanatory research using descriptive analysis and causality test with SPSS tool. The samples of this research are 198 students who had ever got series of subjects related to financial management, investment and capital market. The results have shown that there are differences in the level of financial literacy in students. The results of this study also indicate that the financial literacy of students do not significantly influence their investment decision in the Indonesia Stock Exchange. The high level of financial literacy on the students is not the only factor in investment decision making. There are other factors that also influence the student investment decision making when investing in The Indonesia Stock Exchange.